2001
DOI: 10.1002/chir.1023
|View full text |Cite
|
Sign up to set email alerts
|

Is (9Z)‐“meso”‐zeaxanthin optically active?

Abstract: The question raised in the title was answered. (3R, 3'S)-meso-Zeaxanthin was submitted to iodine catalyzed photochemical stereoisomerisation. The enantiomeric (9Z) and (9'Z) geometrical isomers were isolated by semipreparative HPLC and separated as diastereomeric dicarbamates on a chiral column only. Cleavage of the carbamate could not be effected. CD-Spectra of (1"S, 1"S)- and (1"R, 1"R)-dicarbamates of geometrical isomers of (3R, 3'R)- and (3R, 3'S)-meso-zeaxanthin were systematically studied and the contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…This difference leads to a decoupling of the C‚C bond in the e-ring from the rest of the conjugated chain, resulting in a conjugation length of 10 for lutein and 11 for zeaxanthin. Because of the conjugation length is a key factor to determine many spectroscopic properties of carotenoids (7,10), the stereoisomer (3R,39S-meso)-zeaxanthin is spectroscopically indistinguishable from (3R,39R)-zeaxanthin except under specialized conditions using polarized light, such as circular dichroism spectroscopy (45). We found that XBP complexes with exogenous (3R,39R)-zeaxanthin were considerably more unstable than complexes with the other two xanthophylls, especially after freezing; therefore, the studies reported below generally focused on the interactions of (3R,39R,69R)-lutein and (3R,39S-meso)-zeaxanthin with XBP.…”
Section: Resultsmentioning
confidence: 99%
“…This difference leads to a decoupling of the C‚C bond in the e-ring from the rest of the conjugated chain, resulting in a conjugation length of 10 for lutein and 11 for zeaxanthin. Because of the conjugation length is a key factor to determine many spectroscopic properties of carotenoids (7,10), the stereoisomer (3R,39S-meso)-zeaxanthin is spectroscopically indistinguishable from (3R,39R)-zeaxanthin except under specialized conditions using polarized light, such as circular dichroism spectroscopy (45). We found that XBP complexes with exogenous (3R,39R)-zeaxanthin were considerably more unstable than complexes with the other two xanthophylls, especially after freezing; therefore, the studies reported below generally focused on the interactions of (3R,39R,69R)-lutein and (3R,39S-meso)-zeaxanthin with XBP.…”
Section: Resultsmentioning
confidence: 99%
“…In THF, its CD spectrum is strongest in the UV range (Fig. 6), and the weak signals in the visible range are usually considered to be artifactual (28,29). When dissolved in CHAPS, the UV CD of (3R,3ЈR)-zeaxanthin is no longer detectable, whereas a negative Cotton peak is present at 410 nm, and a biphasic positive Cotton peak is present at 480 and 500 nm.…”
Section: Xanthophyll Binding and Spectral Studies With Gstp1 And Xbp-mentioning
confidence: 99%
“…This difference leads to a decoupling of the C=C bond in the ε‐ring from the rest of the conjugated chain, resulting in a conjugation length of 10 for lutein and 11 for zeaxanthin. Because of the conjugation length is a key factor to determine many spectroscopic properties of carotenoids (7,10), the stereoisomer (3 R ,3′ S ‐meso)‐zeaxanthin is spectroscopically indistinguishable from (3 R ,3′ R )‐zeaxanthin except under specialized conditions using polarized light, such as circular dichroism spectroscopy (45). We found that XBP complexes with exogenous (3 R ,3′ R )‐zeaxanthin were considerably more unstable than complexes with the other two xanthophylls, especially after freezing; therefore, the studies reported below generally focused on the interactions of (3 R ,3′ R ,6′ R )‐lutein and (3 R ,3′ S ‐meso)‐zeaxanthin with XBP.…”
Section: Resultsmentioning
confidence: 99%